Optimasi Produksi Biogas Dari Campuran Kotoran Sapi Dan Rumput Gajah (Pennisetum purpureum) - Nanda Saputra Nikolas; G M Saragih; Hadrah Hadrah (Jurnal Daur Lingkungan, 2021)
This study aims to determine the optimization of biogas production from a mixture of cow dung and elephant grass (Pennisetum Purpureum). Cow manure and fresh elephant grass are taken directly in Teluk Singkawang Village, Sumay District, Tebo Regency, Jambi Province. This research method is the experimental method. There are 4 variations of the mixture in the digester, namely P1 (RG: 25%, KS: 50%, water: 25%), P2 (RG: 50%, KS: 25%, water: 25%), P3 (KS: 75 % and Water: 25%), P4 (RG: 75%, and Water: 25the mixture was put into a digester from a plastic gallon with a volume of 18 liters and tightly closed. The study was conducted for 30 days. The parameters observed in this study included biogas pressure, flame test, daily temperature and initial and final pH. The results showed that the maximum pressure in all digesters I-V were as follows: 705.6 (N/m)2, 689 (N/m)2, 823.2 (N/m2), and in digester IV there was no gas pressure produced. The flame test conducted showed that there was a flame on the digester I-III (with the addition of cow dung) with the flame color, yellowish blue, reddish blue, and blue. Meanwhile, Digester IV (without the addition of cow dung) does not produce a flame. while the initial pH values of all variations were in the normal range, namely 7, 8, 7, 8 for P1, P2, P3 and P4 respectively; while the final pH was 7, 6, 7, 4, respectively. The average daily temperature was almost the same for all variations, namely 27.2 oC, 28.26 oC, 27.74 oC, and 27.94 oC.